Quantitative Estimates on the Domain of Feedback Linearization. Issue 1 (2023) - Jindal, Ashutosh; Banavar, Ravi; Chatterjee, Debasish; Chitre, Ronit M
Abstract: Feedback linearization (FL) is a powerful tool to enable control synthesis for nonlinear systems. Since FL is a local construction, an important notion is the domain of validity of the procedure, and in particular, quantitative estimates of these domain of applicability of the procedure. Such quantification is missing in the existing literature and this article fills in this niche using the mathematical tool of the implicit function theorem. The results provide lower bounds on the region in which a given discrete time system is feedback linearizable.